Green infrastructure in informal unplanned settlements: the case of Kya Sands, Johannesburg. Issue 1 (2nd January 2019) - Adegun, Olumuyiwa Bayode
ABSTRACT: In urban areas, green spaces and natural ecosystems can be a source of benefits to different socio-economic classes of residents, including those within unplanned informal settlements. Using a qualitative research approach, this study brings to light some of the existing green infrastructure (domestic gardens, informal parks, open spaces, stream with wetlands and the riparian corridor) in Kya Sands informal settlement in Johannesburg. It shows the way residents utilise green infrastructure and perceptions of their usefulness. The relevance of green infrastructure in the context of informal unplanned settlements became clearer. In the absence of state interventions, self-help initiatives in greening were observed in the study. Productive collaboration with the state and relevant non-governmental organisations is necessary for upgrading and to overcome limitations of individual initiatives within the community. The paper contributes to the growing body of knowledge on greening in low-income, informal and unplanned urban environments.